2013
DOI: 10.1155/2013/974762
|View full text |Cite
|
Sign up to set email alerts
|

Biliopancreatic Diversion: The Effectiveness of Duodenal Switch and Its Limitations

Abstract: The prevalence of morbidly obese individuals is rising rapidly. Being overweight predisposes patients to multiple serious medical comorbidities including type two diabetes (T2DM), hypertension, dyslipidemia, and obstructive sleep apnea. Lifestyle modifications including diet and exercise produce modest weight reduction and bariatric surgery is the only evidence-based intervention with sustainable results. Biliopancreatic diversion (BPD) produces the most significant weight loss with amelioration of many obesit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(42 citation statements)
references
References 64 publications
1
41
0
Order By: Relevance
“…Our study also has several limitations that should be noted. First, we categorized RYGB and BPD/DS into the GB category because of their malabsorptive and restrictive features . Some studies have found that complication rates for BPD/DS were higher than RYGB , while others found comparable complication rates among them .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study also has several limitations that should be noted. First, we categorized RYGB and BPD/DS into the GB category because of their malabsorptive and restrictive features . Some studies have found that complication rates for BPD/DS were higher than RYGB , while others found comparable complication rates among them .…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that complication rates for BPD/DS were higher than RYGB , while others found comparable complication rates among them . As BPD/DS procedures were performed less common in the USA , the impact of including both RYGB and BPD/DS in the same GB category should be minimal. Upon checking, among the 71 studies included in our meta‐analyses, only three studies included BPD/DS, and after excluding them from the analyses, the complication rates did not vary, except for rates for Leak (from 1.14% to 1.12%) and mortality from PE (from 0.22% to 0.24%).…”
Section: Discussionmentioning
confidence: 99%
“…EBWL was reported to reach 69%, 73%, and 66% after 1 year, 3 years, and 5 years of follow-up 25 . Overall, multiple series about BPD/DS have reported 61% to 85% EBWL at moderate term follow-up 26 .…”
Section: Discussion:-mentioning
confidence: 99%
“…Other cardiometabolic risk factors, including hypertension and dyslipidemia, have also shown marked improvement following BPD/DS. Additionally, obstructive sleep apnea was resolved in the majority of patients 26 .…”
mentioning
confidence: 89%
“…Type 2 diabetes (T2DM) is the most common form of diabetes, leads to many health problems including cardiovascular disease, stroke, blindness, kidney failure, neuropathy, amputations, impotency, depression, cognitive decline and mortality risk from certain forms of cancer and its prevalence throughout the world has been in direct association increase rates of obesity worldwide (2). Current therapy for type 2 diabetes includes lifestyle intervention (weight-loss, appropriate diet, exercise), anti-diabetes medication(s) or metabolic surgery (3).…”
Section: Introductionmentioning
confidence: 99%